2019
DOI: 10.1177/1179551418825037
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Converting Enzyme Gene Insertion/Deletion Polymorphism Is Not Responsible for Antihypertensive Therapy Induced New Onset of Type 2 Diabetes in Essential Hypertension

Abstract: Background:Antihypertensive drug therapies have been reported to be associated with new onset of type 2 diabetes mellitus in some hypertensive patients after prolonged use. Angiotensin converting enzyme (ACE) gene has been found to affect essential hypertension, response of antihypertensive therapies, and glycemic disturbances. Therefore, ACE gene I/D polymorphism may be associated with risk of new onset of type 2 diabetes via metabolic disturbances, glycemic dysregulation, and insulin resistance.Aim:To assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The remaining 91 articles were subject to a complete full-text assessment, and as a result, 34 articles were excluded due to the following reasons: (1) theoretical research (11); (2) without clinical outcomes (18); (3) repeated articles (2); and (4) lack of a control group (3). We ultimately identified 57 studies 662 that met the inclusion criteria of the current meta-analysis, which incorporated a total of 16,298 EH patients in the EH group and 16,564 healthy controls or patients without EH in the control group. Study selection is outlined in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The remaining 91 articles were subject to a complete full-text assessment, and as a result, 34 articles were excluded due to the following reasons: (1) theoretical research (11); (2) without clinical outcomes (18); (3) repeated articles (2); and (4) lack of a control group (3). We ultimately identified 57 studies 662 that met the inclusion criteria of the current meta-analysis, which incorporated a total of 16,298 EH patients in the EH group and 16,564 healthy controls or patients without EH in the control group. Study selection is outlined in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“… 12 Another found blood pressure with new onset T2D and essential hypertension to have no association with the ACE I/D polymorphisms. 13 A recent meta-analysis found that ACE I/D polymorphism was associated with insulin-resistant polycystic ovarian syndrome, especially among Asians. 14 It is important to note that the exact relationship between ACE I/D polymorphisms and metabolic indicators could vary depending on several other variables such as population demographics, study design, and other genetic or environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“… 12 In two separate meta-analyses, Ng et al reported that there was a noticeable protective role of the II genotype against diabetic nephropathy, especially among T2DM patients of Asian (Chinese, Japanese, and Korean) descent compared to Caucasians. 13 , 14 The authors reported that the presence of the ACE II genotype among Asians with T2DM was also associated with a lower risk of macroalbuminuria but was slightly associated with the risk of microalbuminuria. There is limited research that has validated these findings.…”
Section: Introductionmentioning
confidence: 99%
“…22 ACE II genotype is associated with a significant decrease in hypertension, in contrast to the DD genotype. 23 ACE I/D polymorphism indirectly affects the regulation of lipids. 24 ACE is connected with some cardiovascular abnormalities such as myocardial infarction, 25 cardiovascular diseases, 26 strokes and coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%